2001
DOI: 10.1111/j.1572-0241.2001.03467.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin E and Eosinophilic Cationic Protein in Segmental Lavage Fluid of The Small and Large Bowel Identify Patients With Food Allergy

Abstract: In endoscopically guided segmental lavage fluid, IgE and ECP/protein are increased in patients with food allergy. These measurements seem to offer an attractive diagnostic tool and may serve as a screening method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
4

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 22 publications
0
52
0
4
Order By: Relevance
“…However, if these tests are negative, the reactions may still be IgE-mediated [12]. Several recent studies have shown that IgE may be detectable in intestinal lavage fluid and biopsy specimens even if the amount is too small or transient to be detectable in blood [5,6,7]. Hence, apparent non-IgE-mediated adverse reactions to food may actually be local IgE-mediated allergic reactions of the intestine [3, 4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, if these tests are negative, the reactions may still be IgE-mediated [12]. Several recent studies have shown that IgE may be detectable in intestinal lavage fluid and biopsy specimens even if the amount is too small or transient to be detectable in blood [5,6,7]. Hence, apparent non-IgE-mediated adverse reactions to food may actually be local IgE-mediated allergic reactions of the intestine [3, 4].…”
Section: Discussionmentioning
confidence: 99%
“…Immediate responses such as luminal influx of fluid and mucosal oedema have not been described in non-IgE-mediated intestinal food allergy. However, studies indicate that local IgE may be detectable in allergic reactions of the intestines [5,6,7], suggesting that immediate hypersensitivity reactions might be IgE-mediated despite negative skin prick test (SPT) and lack of systemic food-specific IgE.…”
Section: Introductionmentioning
confidence: 99%
“…Food allergy was only diagnosed when food-specific sensitization was detectable by positive skin-prick test, serum IgE (≥class II) or proof of intestinal IgE by endoscopically guided segmental lavage [2,16,20] in conjunction with a reproducible clinical adverse reaction to the food antigen(s) applied. Food antigens identified were cereals, soy, nuts, milk, beef, pork, egg and pollen-cross reactive allergens (apple, celery, etc.).…”
Section: Methodsmentioning
confidence: 99%
“…[1,2,3]. One possible pathway represents the degranulation of mast cells and the consecutive release of mediators and proteases followed by an enhancement of the intestinal mucosal permeability resulting in an increased influx of potential allergens and harmful microbes into the intestinal tissue [4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…4). Analysis of the lavage fluid (results are given per mg of protein) revealed increased production of immunoglobulin E (IgE) locally in the gut (4.2 U, normal < 0.35 [2,3]) and increased eosinophilic cationic protein levels (18.8 µg, normal < 4.5). Histologic examination was able to rule out infection, mastocytosis, and eosinophilic gastroenteritis, but showed increased numbers of mast cells (1066/mm 2 , normal < 600) and eosinophils (876/mm 2 , normal < 200).…”
mentioning
confidence: 99%